Kinect Depth Image Processing for Hand Motion Recognition using Backpropagation Neural Network - Syamsiar Kautsar; Purwadi A. Darwito; Sryang T. Sarena (Institut Teknologi Sepuluh Nopember, 2015)
Kinect RGB-D Camera is a sensor for human gesture recognition. Kinect has built-in infrared array sensor which produces a depth image data. In this research, the depth image data is used to recognize human hand condition. The depth images of human right hand are processed by normalized central moment method. Furthermore, the moment value of hand depth image is used for backpropagation artificial neural network data training. A great training result is yielded by 70% accuracy. In addition, the output of neural netwok model is used to control a robot hand.